Current status of reference location in the basic model for assessment of external radiation doses to the population living in radioactively contaminated areas after the Chernobyl accident - A. N. Barkovsky; V. P. Ramzaev (Радиационная гигиена)
An open plot of virgin land is the reference location in the basic model used to date to estimate the effective dose of external exposure to the population living in a radioactively contaminated area. As our field observations in the Bryansk region of Russia have shown, at present it is very difficult to find truly reference plots of virgin land due to the fact that many virgin meadows were plowed or reclaimed for more than 30 years after the Chernobyl accident. Without special instrumental survey, such disturbed meadow areas can easily be confused with areas of virgin soil. Therefore, the situation with the use of open areas of virgin soil as the reference location has changed dramatically since the first years after the Chernobyl accident. It requires a change in the approach to choosing such a location for the model and/or some revision of the structure of the model itself. Firstly, we propose and justify the use of a permanently cultivated kitchengarden plot as the reference location. The second way to resolve the current difficult situation with the presence of a sufficient number of the virgin soil sites could be excluding the very concept of “reference location” from the model. In this case, when calculating the effective dose of external radiation, it is proposed to directly use the values of the gamma radiation dose rate in the air normalized to the 137Cs contamination density of soil. The values of the normalized dose rate should be experimentally determined in the required time period for each of the locations taken into account in the model.